2013
DOI: 10.1029/2012ja018122
|View full text |Cite
|
Sign up to set email alerts
|

On the nature of low‐latitude Es influencing the genesis of equatorial plasma bubble

Abstract: [1] The potential influence of the postsunset low-latitude sporadic E (E s ) on the genesis of equatorial plasma bubble (EPB) has been investigated using observations made with the Gadanki radar and two ionosondes, one located at the magnetic equator providing the F layer characteristics and another at magnetically low-latitude providing the E s parameters. Observations revealed that the occurrence of EPB was associated with either the disruption of E s or presence of nonblanketing-type E s or intermittently o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
24
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 13 publications
(25 citation statements)
references
References 22 publications
1
24
0
Order By: Relevance
“…On the other hand, a very recent paper by Joshi et al . [] highlighted the role of the E sporadic ( E s) in the genesis of equatorial plasma bubbles also during nighttime. Our results indicate that the daytime amplitude scintillations are concentrated in the interval 09:00–14:00 UT (05:00–10:00 LT) (Figure ), when E s layers are often observed by the AIS‐INGV ionosonde.…”
Section: Summary and Discussionsupporting
confidence: 86%
“…On the other hand, a very recent paper by Joshi et al . [] highlighted the role of the E sporadic ( E s) in the genesis of equatorial plasma bubbles also during nighttime. Our results indicate that the daytime amplitude scintillations are concentrated in the interval 09:00–14:00 UT (05:00–10:00 LT) (Figure ), when E s layers are often observed by the AIS‐INGV ionosonde.…”
Section: Summary and Discussionsupporting
confidence: 86%
“…Recently, Joshi et al . [, ] have reported that the presence of the blanketing‐type E s in the low latitudes can suppress the genesis of the EPBs and plays an important role in explaining the day‐to‐day variability of the ESF. Also, the low‐latitude E region conductivity has been known to influence the evening electrodynamics related with the prereversal enhancement (PRE).…”
Section: Resultsmentioning
confidence: 99%
“…It must be mentioned here that 19:30 IST to 20:30 IST is usually the time of the F layer attaining the peak height due to the PRE and also the time of the genesis of the EPB. Possibly, the occurrence of the Es b over Sriharikota during that period in category 2 cases resulted in the suppression of the EPB genesis over Sriharikota longitude by short circuiting the polarization electric field [ Stephan et al ., ; Joshi et al ., , ]. Spatial observation of low‐latitude E s could not be made with the current observational setup used for the investigation.…”
Section: Resultsmentioning
confidence: 99%
“…Also, no E s layer disruption occurs when PRE amplitude decreases or is inhibited under DDEFs. Recently Joshi, Patra, Pant, and Rao () have investigated the possible connection between low‐latitude E s layers and EPBs during geomagnetically quiet days over Indian sector. Their results also indicate that when blanketing type E s occurs at low latitudes for long duration in the sunset hours, significant rise in PRE height is not observed resulting in absence of EPBs.…”
Section: Discussionmentioning
confidence: 99%
“…They suggested that the E and F region coupling around sunset could affect strongly the linkage between PRE drifts and E s layer disruption or formation. Using Sriharikota ionosonde, Joshi, Patra, and Rao () and Joshi, Patra, Pant, and Rao () have examined the role of quiet time low‐latitude E s layer activity on the generation of ESF irregularities around the sunset terminator over India. They suggested that E s layers play significant role in the occurrence of ESF irregularities in the sunset terminator depending upon the type of E s layer.…”
Section: Introductionmentioning
confidence: 99%